Avaliação da atividade antinociceptiva e anti-inflamatória dos extratos da alga Caulerpa kempfii (CAULERPACEAE) - Falcão , Maria Alice Pimentel (2014)
Marine organisms are a rich source of new prototype drugs. Among them, the seaweeds show different morphological, structural and metabolic features. The aim of this study was to investigate antinociceptive and anti-inflamatory activities of the hexanic (HE), acetate of ethil (AE) and methanolic (ME) extracts of Caulerpa kempfii. The acetic acid-induced writhing test, hot plate test and formalin-induced nociception were carried out to evaluate the antinociceptive potential of these extracts, while the carrageenan-induced peritonitis was applied to investigate an anti-inflammatory activity of C. kempfii extracts. In the acetic acid-induced writhing, HE, AE, ME and dipyrone induced writhing inhibition of 76,7; 77,9; 90,8 and 89,3%,,respectively. In the hot plate test, C. kempfii extracts did not increase the latency time of the animals in the time evaluated. In the neurogenic phase the extracts induced significant inhibition of de 28% (HE), 37,4% (AE) e 35,9% (ME). In the inflammatory phase was reduced significantly 55,1% (HE); 44,5% (AE) and 54,9% (ME) respectively, while indomethacin inhibited 62,6%. Moreover, in the carrageenan-induced peritonitis, a reduction of cell migration was seen in all extracts evaluated 27% (HE); 54,1% (AE); 26,0% (ME); 67,1% (indomethacin). Thus, the present results allow concluding that the HE, AE and ME from macro alga C. kempfii have anti-inflammatory and antinociceptive properties and may be used as prototypes of drugs, natural medicines or herbal remedies.